2016
DOI: 10.1073/pnas.1606267113
|View full text |Cite
|
Sign up to set email alerts
|

β-arrestin–biased signaling through the β 2 -adrenergic receptor promotes cardiomyocyte contraction

Abstract: β-adrenergic receptors (βARs) are critical regulators of acute cardiovascular physiology. In response to elevated catecholamine stimulation during development of congestive heart failure (CHF), chronic activation of G s -dependent β 1 AR and G i -dependent β 2 AR pathways leads to enhanced cardiomyocyte death, reduced β 1 AR expression, and decreased inotropic reserve. β-blockers act to block excessive catecholamine stimulation of βARs to decrease cellular apoptotic signaling and normalize β 1 AR expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 48 publications
3
86
0
Order By: Relevance
“…Propranolol, as a non-selective beta-blocker, blocks the β-adrenoceptor signaling pathway which is coupled to a G-protein ,but prefers to activate the β-arrestin dependent signaling pathway which is independent of G protein. This mechanism is similar to that seen with the non-selective betablocker/alpha-1 blocker, carvedilol, and the selective β2 adrenergic receptor antagonist, ICI118551 [10,16].…”
Section: Introductionsupporting
confidence: 63%
“…Propranolol, as a non-selective beta-blocker, blocks the β-adrenoceptor signaling pathway which is coupled to a G-protein ,but prefers to activate the β-arrestin dependent signaling pathway which is independent of G protein. This mechanism is similar to that seen with the non-selective betablocker/alpha-1 blocker, carvedilol, and the selective β2 adrenergic receptor antagonist, ICI118551 [10,16].…”
Section: Introductionsupporting
confidence: 63%
“…However, the cardiac β 2 AR-G i -Akt signaling is traditionally considered beneficial to myocardium relative to cardiac toxicity induced by β 1 AR signaling [27]. β 2 AR agonist promotes Akt activity to protect against myocyte apoptosis induced by oxidative stress or overactivated β 1 AR signaling in I/R [8486]. Meanwhile, stimulation of β 2 AR with formoterol also activates eNOS and augments NO bioavailability, which attenuates myocardial cell death after I/R [87].…”
Section: Insulin and βAr Signaling In Ischemia And Reperfusionmentioning
confidence: 99%
“…The β 2 AR-G i signaling pathway plays a crucial role in the regulation of cell proliferation and protection against cardiomyocyte apoptosis via transactivation of a PI3K-Akt signaling pathway. The β 2 AR-G i signaling pathway also attenuates the βAR-G s -mediated inotropic response via inhibition of AC activity [86]. Meanwhile, adrenergic signaling also activates PKA and Akt to promote glucose uptake in heart[10, 11].…”
Section: Figurementioning
confidence: 99%
“…Both βAR isoforms rely on G protein-independent, GRK/βarr-dependent signaling to promote Src- and MMP-mediated HB-EGF shedding and subsequent EGFR activation 15, 16, 39, 64 . In addition, PI3K-dependent Src activation is required for β2AR-mediated EGFR transactivation and significantly increases their association in a multi-receptor complex 44 .…”
Section: Impact and Implications Of Gpcr-dependent Egfr Transactivationmentioning
confidence: 99%
“…The orthosteric non-selective β-blocker carvedilol has been shown to induce βarr-biased βAR-mediated signaling, including EGFR transactivation 6870 ; however, these studies were performed either in HEK 293 cell systems with exogenous receptor expression or in whole heart using a very high dose of carvedilol with no functional insight at a contractile level. Indeed, it has recently been demonstrated that carvedilol does not enhance cardiomyocyte contractility 64 , likely due to its inverse agonist properties 71 . Further, a recent meta-analysis revealed a lack of clinical difference between carvedilol versus the unbiased β-blocker metoprolol succinate in HF patients 72 .…”
Section: Impact and Implications Of Gpcr-dependent Egfr Transactivationmentioning
confidence: 99%